1990
DOI: 10.1037/0033-295x.97.3.432
|View full text |Cite
|
Sign up to set email alerts
|

On the association between connectionism and data: Are a few words necessary?

Abstract: Parallel distributed processing (PDF) models represent a new and exciting approach to the study of visual word recognition in reading. Seidenberg and McClelland's (1989) model is examined because the strongest and widest claims for the viability of a connectionist account of visual word recognition have been made on the basis of their model. The current implemented version of their model fails to account for important facts concerning how human subjects read aloud and carry out lexical decisions, despite the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
220
2
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(232 citation statements)
references
References 43 publications
8
220
2
2
Order By: Relevance
“…With the advent of parallel distributed processing models, some theorists claim that there are no lexicons (e.g., Seidenberg & McClelland, 1989; others dispute this claim (e.g., Besner, Twilley, McCann, & Seergobin, 1990;Coltheart, Curtis, Atkins, & Haller, 1993). The "no lexicon" view would seem to predict that, provided that words and nonwords are matched for orthographic and phonological characteristics, there ought to be no lexical effects in the serial order recall of a patient with no access to semantics.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of parallel distributed processing models, some theorists claim that there are no lexicons (e.g., Seidenberg & McClelland, 1989; others dispute this claim (e.g., Besner, Twilley, McCann, & Seergobin, 1990;Coltheart, Curtis, Atkins, & Haller, 1993). The "no lexicon" view would seem to predict that, provided that words and nonwords are matched for orthographic and phonological characteristics, there ought to be no lexical effects in the serial order recall of a patient with no access to semantics.…”
Section: Discussionmentioning
confidence: 99%
“…What would be needed to see if the combination works is a quantitative examination of whether the values of wordness produced by the lexical model map into drift appropriately (cf. criticism of Seidenberg & McClelland's [1989] model by Besner, Twilley, McCann, & Seergobin [1990]). Thus, the following discussion suggests only possible beginning points for research.…”
mentioning
confidence: 99%
“…If the match value is above a criterion, a "word" response is produced, and if not, a "nonword" response is produced. To account for the effects of type of nonword, Seidenberg and McClelland (1989) proposed that when the nonwords are pseudowords, phonological as well as orthographic output is assessed, but this was not implemented (see the critique by Besner et al, 1990, and the reply by Seidenberg & McClelland, 1990). Error responses come from high-match values when nonwords are presented and low-match values when a word is presented.…”
mentioning
confidence: 99%
“…Wholeword spelling-to-sound correspondences are stored in the lexicon, whereas subword correspondences are computed by a separate route that converts graphemes to phonemes. Although this assumption remains subject to an ongoing debate (e.g., Balota & Spieler, 1998;Besner, 1999;Besner, Twilley, McCann, & Seergobin, 1990;Plaut, 1999;Seidenberg & McClelland, 1989b;Seidenberg & Plaut, 1998;Spieler & Balota, 1997), it is not unique to the symbolic account of reading. Zorzi, Houghton, and Butterworth (1998) demonstrated that the segregation of the sublexical and the lexical routes facilitates the acquisition of spelling-to-soundregularities by a feedforward twolayer network.…”
Section: Does the Mapping Of Graphemes To Phonemes Appeal To Variables?mentioning
confidence: 99%
“…Contrary to this prediction, connectionist accounts of word reading have gained considerable success in modeling the pronunciation of both words and nonwords. The model of Seidenberg and McClelland (1989a) captures the pronunciation of monosyllabic words, although its ability to account for nonword pronunciation is limited (Besner et al, 1990;Coltheart et al, 1993). However, the subsequent models of Plaut et al (1996) and Harm and Seidenberg (1999) account quite well for both monosyllabicword and nonword pronunciation (but see Balota & Spieler, 1998;Besner, 1999;Plaut, 1999;Spieler & Balota, 1997).…”
Section: The Success Of Pattern Associator Accounts Of Readingmentioning
confidence: 99%